2013
DOI: 10.1111/are.12363
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory effect of thyroid hormones improves larval development and reproductive performance in alligator gar (Atractosteus spatula) and spotted gar (Lepisosteus oculatus)

Abstract: Development of alligator gar (Atractosteus spatula) and spotted gar (Lepisosteus oculatus) larvae was evaluated after exposure of embryos to thyroid hormones (TH) by two different methods of administration. For the first method, alligator gar embryos were placed in a water bath with triiodothyronine (T3; 1 ppm for 2 h), and control treatment embryos were placed in a water bath without T3. For the second method, spotted gar adult males and females were injected with different TH during induced spawning: a group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…To date, several species of gar have been spawned in captivity via injection of gonadotropin releasing hormone (GnRH), which acts as an analogue to natural spawning hormones (Mendoza et al 2008;Amores et al 2011;Castillo et al 2013;David et al 2015). Documentation of breeding events in captivity that are not induced via administration of a hormone stimulus is much rarer.…”
mentioning
confidence: 99%
“…To date, several species of gar have been spawned in captivity via injection of gonadotropin releasing hormone (GnRH), which acts as an analogue to natural spawning hormones (Mendoza et al 2008;Amores et al 2011;Castillo et al 2013;David et al 2015). Documentation of breeding events in captivity that are not induced via administration of a hormone stimulus is much rarer.…”
mentioning
confidence: 99%
“…Thyroid hormone accelerated development of the digestive structures, which increased digestive enzyme production at the beginning of exogenous feeding in alligator gar Atractosteus spatula and spotted gar Lepisosteus oculatus thereby imparting improvements in food utilization during the critical time of first‐feeding (Castillo et al . ). Faster digestive tract development and higher digestive enzymes activities during larval development may result in a higher capacity to digest more complex nutrients, promoting growth and increasing nutrient storage and survival rate of fish larvae.…”
Section: Discussionmentioning
confidence: 97%
“…Larval development to a fingerling depends on a proper development of digestive functions during larval life, and digestive tract maturation of can be altered by diet composition (Ma, Cahu, Zambonino, Yu, Duan, Le Gall & Mai 2005). Faster digestive tract development and higher digestive enzyme activities during larval development may result in a higher capacity to digest more complex nutrients, promoting growth and increasing nutrient storage, thereby increasing the survival rates of fish larvae (Castillo, Bollfrass, Mendoza, Fontenont, Lazo, Aguilera & Ferrara 2015). Thyroid hormones stimulated digestive processes in fish and lead to an enhanced absorption of ingested amino acids and peptides (Solbakken, Norberg, Watanabe & Pittman 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Castillo et al. () found that thyroid hormone treatments for broodfish and eggs improved reproductive performance and larval fitness, respectively. However, broodfish production has been considered an impediment to aquaculture due to the species’ protracted time to maturation (A. M. Ferrara and coworkers, paper presented at the World Aquaculture Society's Aquaculture America meeting, 2015).…”
mentioning
confidence: 99%
“…Alligator Gar aquaculture has been studied by a group at the Universidad Aut onoma de Nuevo Le on, Mexico, who have spawned the species in captivity since 1982 (Mendoza et al 2008b) and developed an immunological method for gender identification (Mendoza et al 2012). Castillo et al (2015) found that thyroid hormone treatments for broodfish and eggs improved reproductive performance and larval fitness, respectively. However, broodfish production has been considered an impediment to aquaculture due to the species' protracted time to maturation (A. M. Ferrara and coworkers, paper presented at the World Aquaculture Society's Aquaculture America meeting, 2015).…”
mentioning
confidence: 99%